Peran Fear of Missing Out (FOMO) dalam Hubungan antara Affiliate Marketing dan Impulse Buying pada Generasi Z - Annisa Desty Puspatriani; Bella Pratiwi Rachman; Muis Wirasujatma (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study aims to examine the influence of fear of missing out (FoMO) and content marketing on impulse buying among Generation Z skincare consumers on TikTok Shop in Jakarta, while simultaneously comparing the relative strength of both factors within a single integrated empirical model. This research is particularly relevant given the limited number of studies that jointly examine internal psychological factors and external marketing stimuli within Indonesia's social commerce context. A quantitative approach with an online survey design was employed to collect data from 405 respondents aged 18 to 28, which were subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both variables exert a positive and significant effect on impulse buying, with content marketing demonstrating a stronger contribution than FoMO. These results suggest that the quality of promotional content holds a more strategic role than psychological pressure alone in driving spontaneous purchasing decisions. This study offers theoretical contributions by integrating internal and external factors simultaneously to explain consumer behavior within Indonesia's rapidly growing social commerce platforms, and provides practical guidance for businesses designing more effective digital marketing strategies.